Best Answer

Is this a system of equations?

2X + 5Y = 4

X + 5Y = 7

solve for X using bottom equation

X = 5Y - 7

insert into top equation

2(5Y - 7) + 5Y = 4

distribute

10Y - 14 + 5Y = 4

solve for Y

15Y = 18

Y = 18/15 = 6/5

use bottom equation to find X

X +5(6/5) = 7

X = 1

check with bottom equation

1 + 5(6/5) = 7

7 = 7

not true for top equation

( sorry, I forgot what happens then-resubmit question )

Q: What does 2x plus 5y equal 4 and x plus 5y equal 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

8x + 20y

y=x+5

2X + 5Y = 205Y = - 2X + 20Y = (- 2/5)X + 4================now, reading off the function,Y intercept = 4===========

(4, -1)

3x + 4y - 5z and -2x - 5y + 4z Added together, give (3-2)x + (4-5)y + (-5+4)z = x - y - z

Related questions

-2x = 20 + 5y-2x - 20 = 5y-2/5x - 4 = yX Intercept = (-10,0) or -10Y Intercept = (0,-4) or -4

8x + 20y

y=x+5

2X + 5Y = 205Y = - 2X + 20Y = (- 2/5)X + 4================now, reading off the function,Y intercept = 4===========

(4, -1)

2x+5y=20 Solve for y -2x -2x 5y=20-2x 5 5 5 y=4-2x 5

3x + 4y - 5z and -2x - 5y + 4z Added together, give (3-2)x + (4-5)y + (-5+4)z = x - y - z

x = 4 and y = -1 (4. -1)

2X+5Y+30=0 So you subtract 30 from each side. 2X+5Y+30-30=0-30. So you know 2X+5Y=-30. now there are many different possibilities for X and Y unless there is a specification. here are some possibilities=X=0,Y=6 or X=A5,Y=0 or X=5,Y=4

2.6

If 2x+5y = 4 and y^2 = x+4 then by combining the equations into a single quadratic equation and solving it the points of contact are made at (12, -4) and (-7/2, 3/2)

You are given: 2x + 5y = 3 -x + 3y = -7 Multiply the second equation by 2, so now your two equations look like this: 2x + 5y = 3 -2x + 6y = -14 Now add these two equations together and solve for your remaining variable: 11y = -11 y = -1 Finally, plug this value for y into either of the original equations and solve for x: 2x + 5y = 3 2x + (5)(-1) = 3 2x - 5 = 3 2x = 8 x = 4 So your final answer is x = 4 and y = -1.